Semantic Analysis of The Relation of The Meaning of The Words Human and Jinn in The Qur'an - Annisa, Maryam Nur; Usman, Mohamad Alil; Kiswanto, Dudi (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2023)
The purpose of this study was to uncover the meaning of the words human and jinn as well as the relation of meaning between the words human and jinn mentioned in the Qur'an. The words human and jinn are repeatedly mentioned in the Qur'an and are often found side by side. Of course, there is a connection of meaning between the two. The purpose of uncovering the relation of the meanings of the words